Dar dėl an tipo junginių siaurinimo - Zinkevičius, Zigmas (Baltistica, 1976)
Some further notes on the narrowing of the an-type clusters The article presents a development of the ideas dealt with by the author in Baltistica, I Priedas (p. 227–231). The isophone of the change of an, am, en, em > un, um, in, im in the south up to the river Šventoji coincides with the old border between the provinces of Vilnius and Trakai (the line is taken as indicated in the maps of the Grand Duchy of Lithuania drawn by J. Jakubowski and M. Liubawski). In the opinion of the author this is one of the earliest isophones of dialectal division of Lithuanian. To the north of the Šventoji this isophone diverges into some smaller ones reflecting different degrees of the аn-narrowing. The administrative boundary itself appears to have been unstable – it was being moved westward with the peopling of the then continuous forest area. Thus there is reason to believe that there the diversity of the аn-narrowing depends on the instability of the administrative boundary.